Case Report: Abdominal Cocoon With Jejuno-Ileo-Colonic Fistula - Jiao, Jian; Shan, Keshu; Xiao, Kun; Liu, Zhenjun; Zhang, Ronghua; Dong, Kangdi; Liu, Jin; Teng, Qiong; Shang, Liang; Li, Leping (Frontiers in Surgery, 2022)
Introduction: Abdominal cocoon is a unique peritoneal disease that is frequently misdiagnosed. The occurrence of abdominal cocoon with a jejuno-ileo-colonic fistula has not been previously reported. Case Presentation: We admitted a 41-year-old female patient with abdominal cocoon and a jejuno-ileo-colonic fistula. She was admitted to our hospital for the following reasons: “the menstrual cycle is prolonged for half a year, and fatigue, palpitations, and shortness of breath for two months”. On the morning of the 4th day of admission, the patient experienced sudden, severe intolerable abdominal pain after defecating. An emergency abdominal CT examination revealed intestinal obstruction. Surgery was performed, and the small intestine and colon were observed to be conglutinated and twisted into a mass surrounded by a fibrous membrane, and an enteroenteric fistula was observed between the jejunum, ileum and sigmoid colon. We successfully relieved the intestinal obstruction and performed adhesiolysis. The patient was discharged from our hospital on the 6th postoperative day, then she recovered and was discharged from Feicheng People's Hospital after another 11 days of conservative treatment, and she recovered well during the 2-month follow-up period. Conclusion: Abdominal cocoon coexisting with a jejuno-ileo-colonic fistula is very rare. During the process of treating abdominal cocoon, the patient's medical history should be understood in detail before the operation, and the abdominal organs should be carefully evaluated during the operation to avoid missed diagnoses.